Non-binding norms in international humanitarian law efficacy, legitimacy, and legality - Crawford, Emily (Writer on international law) (Oxford monographs in international humanitarian and criminal law., 2021)
This monograph examines and analyses the phenomenon of non-binding instruments (also known as 'soft law') in the law of armed conflict, or international humanitarian law. It covers the benefits and drawbacks for States and non-States actors as well as their effectiveness and development in the context of armed conflict.